1994
DOI: 10.1037/0021-843x.103.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Measuring impulsivity and examining its relationship to delinquency.

Abstract: A multimethod, multisource assessment of impulsivity was conducted in a sample of more than 400 boys who were members of a longitudinal study of the development of antisocial behavior. Exploratory and confirmatory factor analysis of the 11 different impulsivity measures revealed two impulsivity factors: Cognitive and Behavioral. Cognitive and behavioral impulsivity had similar correlations with socioeconomic status. Cognitive impulsivity was more strongly related to IQ than was behavioral impulsivity. Behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
506
5
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(554 citation statements)
references
References 62 publications
32
506
5
11
Order By: Relevance
“…The delinquency seriousness classification of official reports was guided by the Index of Crime Seriousness (ICS; White et al, 1994;Wolfgang, Figlio, Tracey, & Singer, 1985). Level 0 consisted of no delinquency.…”
Section: Methodsmentioning
confidence: 99%
“…The delinquency seriousness classification of official reports was guided by the Index of Crime Seriousness (ICS; White et al, 1994;Wolfgang, Figlio, Tracey, & Singer, 1985). Level 0 consisted of no delinquency.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have demonstrated that hyperactivity-impulsivity symptoms are more associated with conduct problems than are inattention symptoms (Babinski, Hartsough, & Lambert, 1999) or that a measure of behavioral impulsivity (a lack of behavioral control) was more associated with delinquency than one of cognitive impulsivity (a lack of planful cognitive performance) (White et al, 1994). It is plausible that the presence of hyperactive-impulsive symptoms of ADHD are associated with general deviant or delinquent behavior, and therefore the risk for substance abuse from hyperactivity-impulsivity would not be specific, but more generally due to an overlap in deviant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to interpret the nature of these general deficits. If we refer to the existing literature that shows differences in cognitive functioning between obese and non-obese people (e.g., Nasser et al, 2004;Nederkoorn, Braet, et al, 2006), it could be argued that obese persons have a fundamental inhibition problem, corresponding to a high level of impulsivity (Horn, Dolan, Elliott, Deakin, & Woodruff, 2003;Stein, Hollander, DeCaria, & Trungold, 1991;Visser, Das-Smaal, & Kwakman, 1996;White et al, 1994). However, the modified shifting task does not allow one to characterize the precise nature of the inhibition deficit: it may be a deficit affecting prepotent response inhibition and/or a deficit affecting resistance to proactive interference (Friedman & Miyake, 2004).…”
mentioning
confidence: 99%
“…The finding of a more pronounced inhibition problem in obese persons with binge eating disorder is of crucial practical importance. Some authors have shown that impulsivity, which is related to inhibitory difficulties (Horn et al, 2003;Stein et al, 1991;Visser et al, 1996;White et al, 1994), predicts overeating (Guerrieri, Nederkoorn, & Jansen, 2007). This tendency to overeat can, in turn, lead to weight gain and to the development of maladaptive strategies to control weight (e.g., dieting, skipping meals).…”
mentioning
confidence: 99%